Investigator-Initiated IBD Trials in the United States: Facts, Obstacles, and Answers. Issue 1 (January 2017) - Herfarth, Hans H.; Jackson, Susan; Schliebe, Barbara G.; Martin, Christopher; Ivanova, Anastasia; Anton, Kristen; Sandler, Robert S.; Long, Millie D.; Isaacs, Kim L.; Osterman, Mark T.; Sands, Bruce E.; Higgins, Peter D.; et al.
Abstract : Abstract: Investigator-initiated randomized clinical trials are the backbone of academic clinical research. Investigator-initiated trials (IITs) complement the large clinical studies sponsored by industry and address questions, which are usually not the main focus of a commercially directed research but have the purpose to confirm, improve, or refute clinically important questions with regard to diagnostic and therapeutic approaches in patient care. The aim of this review is to illustrate the necessary steps to start and complete an IIT in the field of inflammatory bowel diseases in the United States. The initial milestones for an investigator include structuring a protocol, planning and building of the trial infrastructure, accurately estimating the costs of the trial, and gauging the time span for recruitment. Once the trial has begun it is important to keep patient recruitment on target, monitor of the data quality, and document treatment emergent adverse events. This article provides a framework for the different phases of an IIT and outlines potential hurdles, which could hinder a successful execution. Abstract : Article first published online 2 September 2016.